Bilateral elastofibroma dorsi: A rare soft tissue tumor - (:unkn) unknown (My University, 2004)
Elastofibroma, a rare, noncapsulated benign lesion usually arising beneath the rhomboid major and latissimus dorsi muscles subjacent to the inferior angle of the scapula. Recognition of the lesion is important as the differential diagnosis includes other benign and also malignant tumors. A 71-year-old woman was presented with a three year history of mild back pain and bilateral infrascapular swellings. Thorax computed tomography (CT) revealed two poorly circumscribed, heterogenous masses bilaterally located at the infrascapular areas, and magnetic resonance imaging (MRI) confirmed the bilateral involvement. Both masses were excised and diagnosed as elastofibroma. Lesions located deep beneath the inferior tip of the scapula should arouse suspicion of an elastofibroma.
Keywords: Elastofibroma; Soft tissue tumors; Surgery